Editor’s Letter - Sánchez Gutiérrez, José (Mercados y Negocios, 2024)
Welcome to the latest edition of our journal, where we present a diverse array of research articles that delve into contemporary issues across various fields. This issue combines empirical studies and theoretical explorations illuminating different aspects of business, tourism, food preferences, and organizational culture. We aim to provide insightful analyses and foster a deeper understanding of these multifaceted topics